Individual Criminal Responsibility for the Crime of Aggression: The Role of the ICC’s Leadership Clause - Hussain, Nazar; Khan, Asif; Chandio, Liaquat Ali; Oad, Sahib (Pakistan Journal of Humanities and Social Sciences, 2023)
Before the 2010 Kampala Conference, this research study investigates the notion of individual criminal accountability for crimes of aggression. The article examines the qualifications for leadership underneath the ICC leadership clause and dives into the legal concepts of actus reus as well as mens rea as they apply to the act of aggression. The article argues that the ICC's inclusion of the leadership clause is crucial for delegitimizing the act of aggression and holding individuals accountable for their roles in committing it. Through a comprehensive review of legal cases and scholarly literature, this article concludes that the leadership clause serves as a necessary tool for enforcing international criminal law and deterring future acts of aggression. The qualitative research methodology has been applied on following article.